Reduced Pump Power Consumption Micro Accumulating Power Plants - Fakhriddin Nosirov,Urishev B.U,Bozor Ulugov Jakhongir Dustmurodov, Panji Khaliyarov (International Journal of Advanced Science and Technology, 2020)
The main issue when using pumped storage power plants is to increase their efficiency by reducing energy costs in the pump mode. This article proposes a diagram of a micro-hydro accumulative power plant with upper and lower reservoirs, a hydraulic turbine unit, a pumping unit and stepwise arranged hydraulic rams used to supply water from the lower reservoir to the upper one. This arrangement of hydraulic rams allows you to reuse the flowing water from them for feeding into the upper tank. The results of calculations and experimental studies show that the use of two stepwise arranged hydraulic rams allows to supply 20 ... 45% of the water from the lower tank to the upper tank, depending on the height of the lift without electricity consumption. According to the results of the experiments, an analytical dependence is obtained that approximates the process of feeding hydraulic rams of a certain flow of water to a selected lifting height. The energy characteristics of the design of a micro-accumulating power plant, consisting of hydraulic rams and pumping units, which allow you to quickly determine the amount of water supplied to the upper tank and the energy expended for this purpose, and, therefore, the efficiency of the complex as a whole, are proposed. These characteristics can be used to justify the parameters of water supply to the upper tank and the effectiveness of hydraulic water storage.